Productivity Shocks and Repayment Behavior in Rural Credit Markets: A Framed Field Experiment. Issue 10 (2nd October 2020) - Adjognon, Guigonan Serge; Liverpool-Tasie, Lenis Saweda; Shupp, Robert
Abstract: Improving rural credit markets requires a good understanding of the root causes of market failures and taking necessary steps to address them. This paper investigates the role of productivity shocks in borrowers repayment choices. Using a framed field experiment that simulated a repeated interaction in an input credit market, the analysis finds strong evidence that adverse productivity shocks lead to higher default, even when they do not induce negative returns. This relationship is robust to the presence of an information exchange system enforcing dynamic incentives. The findings suggest that recurrent shocks such as those resulting from the harmful effects of climate change could exacerbate failures in rural credit markets, undermining hard-won progress toward rural financial inclusion.